2013
DOI: 10.1186/1748-717x-8-283
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of therapeutic index for brain tumors with daily image guidance

Abstract: BackgroundImage-guidance maximizes the therapeutic index of brain irradiation by decreasing setup uncertainty. As dose-volume data emerge defining the tolerance of critical normal structures responsible for neuroendocrine function and neurocognition, minimizing clinical target volume (CTV) to planning target volume (PTV) expansion of targets near these structures potentially lessens long-term toxicity.MethodsWe reviewed the treatment records of 29 patients with brain tumors, with a total of 517 fractions analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Shields et al concluded that daily imaging allows application of individualized CTV expansion which decreases dose to OAR and can lead to benefit in terms of neurocognition, learning, and neuroendocrine function. [19] Limitations of the present study include that it is retrospective in nature. Furthermore, the study does not include long-term clinical follow-up of the patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Shields et al concluded that daily imaging allows application of individualized CTV expansion which decreases dose to OAR and can lead to benefit in terms of neurocognition, learning, and neuroendocrine function. [19] Limitations of the present study include that it is retrospective in nature. Furthermore, the study does not include long-term clinical follow-up of the patients.…”
Section: Discussionmentioning
confidence: 94%
“…A study done by Shields et al showed that the first three days of CBCT predicted setup uncertainty for subsequent treatments and permitted customized CTV to PTV expansion although it was not statistically significant. [19] CBCTs were reviewed to assess the added benefit of using a 6D couch over conventional couch (in which shifts are applied in three directions -vertical, longitudinal, and lateral). During CBCT analysis, the shifts which had been applied at the time of treatment were negated and position was set as acquisition position.…”
Section: Discussionmentioning
confidence: 99%
“…Safely reducing planning margins, while adequately treating tumour volumes, can decrease dose to normal brain tissue and critical OAR, leading to better functional outcomes for patients with brain tumours 16. Decreasing the tumour volume may also potentially increase tumour control or reduce radiation‐induced side effects for patients with a meningioma diagnosis 17.…”
Section: Discussionmentioning
confidence: 99%
“…Safely reducing planning margins, while adequately treating tumour volumes, can decrease dose to normal brain tissue and critical OAR, leading to better functional outcomes for patients with brain tumours. 16 Decreasing the tumour volume may also potentially increase tumour control or reduce radiation-induced side effects for patients with a meningioma diagnosis. 17 Although the findings suggest the MFD provides better daily reproducibility statistically, there is not enough clinical significance to suggest one device gives superior daily positioning than the other.…”
Section: Discussionmentioning
confidence: 99%
“…As proton dose distribution is susceptible to the heterogeneity along the beam path, the impact of setup uncertainties is of interest. In the setup of intracranial patients, orthogonal kV and cone-beam computed tomography (CT) are used as image guidance to position the patients under mask [ 19 21 ] and result in a distribution of setup uncertainties. Our current clinical treatment planning system Eclipse (Varian, Palo Alto, California) offers a robust optimization module that optimizes the spot intensities to provide sufficient target coverage under the worst setup and range uncertainty scenarios.…”
Section: Introductionmentioning
confidence: 99%